Fermiology via the electron momentum distribution (Review Article) - Kontrym-Sznajd, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Investigations of the Fermi surface via the electron momentum distribution reconstructed from either angular correlation of annihilation radiation or Compton scattering experimental spectra are presented. The basis of these experiments and mathematical methods applied in reconstructing three-dimensional electron momentum densities from line or plane projections measured in these experiments are described. Finally, papers where such techniques have been applied to study the Fermi surface of metallic materials are reviewed.